Water quality of Bakun Reservoir - Angela Sanoh, Tawan (Universiti Malaysia Sarawak, (UNIMAS), 2014)
A study on water quality was conducted on 8-9 November 2013 and 26-27 February 2014. Three sampling stations were selected at three different depths which represent the water body of the Bakun reservoir. The study is important because there is still not much research on the water quality at Bakun reservoir since the filling started in since 2010.The ex-situ parameters that has been conducted are total suspended solid (TSS), five-days biochemical oxygen demand (BOD5 ), chemical oxygen demand (COD), nitrite-nitrogen (NO,), nitrate-nitrogen (NO,), total kjeldahl nitrogen (TKN), dissolved reactive phosphorus (PO-P), total phosphorus, ammonia-nitrogen (NH3N) and total sulfide. The water quality is different between subsurface and deeper water as pH, temperature, DO, conductivity, turbidity, total suspended solid (TSS), Five-days Biochemical Oxygen Demand (BODs), chemical oxygen demand (COD), Nitrite-Nitrogen (NO5), Nitrate-Nitrogen (NO;), Total Kjeldahl Nitrogen (TKN), dissolved reactive phosphorus (PO±), Total Phosphorus, Ammonia-Nitrogen (NH+N) and total sulfide were significantly different among depths. All parameters showed increasing value as the depth increases except for DO, pH and temperature.